Wczesne wspomaganie rozwoju dziecka z uszkodzonym słuchem jako jeden z warunków jego edukacji włączającej - Jakoniuk-Diallo, Anna; Bączyk, Martyna (Studia Edukacyjne, 2025)
Children with a hearing impairment are a group of persons with disabilities who are often included in the mass education system. For most of them, inclusive education means multiple challenges to overcome. From the early years of development, such students require assistance, which stimulates the development of their psycho-social competences needed to cope with inclusive education. Help may come in the form of early development assistance, focused on helping children and their caretakers, who actively participate in the process.